Proposed cut-off for reactivity of anti-HMGCR and anti-SRP antibodies in patients statin-exposed and statin-unexposed. Issue 35 (August 2018) - Carvalho, Alzira Alves Siqueira; Silva, Vinicius Gomes da; Vieira, Thaiane Fagundes; Delgado, Pamela Oliveira; Corazini, Roseli; Feder, David; Fonseca, Fernando Luiz Affonso
Abstract : Abstract: The therapeutic approach with statins is widely used in the control of dyslipidemias. However, there is no laboratory evaluation to elect patients to make use of this class of therapeutic drugs. We analyzed the prevalence of anti-signal recognition particle (anti-SRP) and anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (anti-HMGCR) antibodies in a heterogeneous cohort of 85 patients in order to determine cutoff reference values for these antibodies. Serum samples from 85 patients were screened for the presence of anti-HMGCR and anti-SRP autoantibodies by enzyme-linked immunosorbent assay. The demographic, clinical, and morphological features were also correlated with anti-HMGCR and anti-SRP antibodies. The patients were divided in 2 groups: A, statin-exposed, and B, statin-unexposed. There was no significant association ( P  > .05) among anti-HMGCR and anti-SRP titers in relation to age, sex, statin exposure, and CK level. The concentrations of both antibodies were not correlated with symptoms, CK level, or statin exposure. Eleven (12.9%) patients had anti-HMGCR antibodies. We found a tendency ( P  = .051) toward greater anti-HMGCR positivity in women with no symptoms. Twelve (14.1%) patients had anti-SRP antibodies. There was no sex predominance, and only 1 patient had muscle complaints. Muscular symptoms were present in 31 (36.5%) patients, 4 (12.9%) were positive for anti-HMGCR antibodies, and 1 (3.2%) was positive for anti-SRP antibodies. A total of 54 (63.5%) patients had no muscle symptoms, 7 (13%) were anti-HMGCR positive, and 11 (20.4%) were anti-SRP positive. We found statistical significance for patients with anti-SRP antibodies when asymptomatic and symptomatic patients were compared ( P  = .029). In contrast, there was no statistically significant difference between symptoms and positivity for anti-HMG antibodies. One of the main aims of this study was to define a cutoff point in a heterogeneous population with different diagnoses. We also demonstrated that anti-HMGCR and anti-SRP antibodies are not 100% specific to immune-mediated necrotizing myopathy. We believe that these antibodies must be tested and interpreted within the specific context. Abstract : Supplemental Digital Content is available in the text